Usefulness of myocardial perfusion SPECT in patients with left bundle branch block and previous myocardial infarction. Issue 9 (15th August 2003) - Candell-Riera, J; Oller-Martínez, G; Pereztol-Valdés, O; Castell-Conesa, J; Aguadé-Bruix, S; Soler-Peter, M; Simó, M; Santana-Boado, C; Soler-Soler, J
Abstract : Background: The diagnostic value of myocardial perfusion scintigraphy in patients with left bundle branch block (LBBB) and previous acute myocardial infarction has not been evaluated. Objective: To determine the utility of single photon emission computed tomography (SPECT) in patients with LBBB and previous acute myocardial infarction. Methods: Seventy two consecutive patients with permanent LBBB and previous acute myocardial infarction were studied with stress-rest SPECT using 99m Tc compounds. The same stress procedures were followed in all patients: (1) exercise alone when it was sufficient; (2) exercise plus simultaneous administration of dipyridamole if exercise was insufficient. Results: In 26 of 28 patients (93%) who had a Q wave acute myocardial infarct before the development of LBBB, there was concordance between abnormal Q waves and rest SPECT in the localisation of myocardial necrosis (κ = 0.836; p = 0.0001). In 48 patients who had coronary angiography, the positive predictive value of exercise (+dipyridamole) myocardial SPECT for the diagnosis of left anterior descending coronary artery stenosis was 93%, for left circumflex coronary artery stenosis, 96%, and for right coronary artery stenosis, 89%. Specificity values were 83%, 91%, and 69%, respectively. However, sensitivity (69%, 64%, and 89%) and negative predictive values (48%, 46%, and 82%) were suboptimal. Conclusions: Rest myocardial perfusion SPECT with technetium compounds is useful for localising healed myocardial infarction in patients with LBBB, and exercise (+dipyridamole) SPECT has a high positive predictive value and specificity for the diagnosis of coronary stenosis in these patients.